NONMEM population pharmacokinetics and Monte Carlo dosing simulations of imipenem in critically ill patients with life‐threatening severe infections during support with or without extracorporeal membrane oxygenation in an intensive care unit. Issue 7 (18th June 2021) - Jaruratanasirikul, Sutep; Boonpeng, Apinya; Nawakitrangsan, Monchana; Samaeng, Maseetoh
Abstract: Study Objectives: The objectives of this study were (i) to determine the population pharmacokinetic (PK) of imipenem in critically ill patients with life‐threatening severe infections, (ii) to investigate the impact of extracorporeal membrane oxygenation (ECMO) on the population PK of imipenem during support with ECMO compared to those without ECMO support, and (iii) to assess the probability of target attainment (PTA) for finding the optimal dosage regimens of imipenem in critically ill patients with life‐threatening severe infections. Design: Open‐label, PK study. Setting: Academic tertiary care medical center. Patients: Fifty critically ill patients with or without ECMO by pooling data from previously published studiesand unpublished data from 14 patients. Intervention and Measurements: The population PK of imipenem was determined using NONMEM and a Monte Carlo simulation was performed to determine the PTAs of achieving 40% and 75% exposure times during which the plasma drug concentrations remained above the MIC. Main Results: The values of volume of distribution and total clearance were 30.5 L and 13.3 L/h, respectively. The ECMO circuit did not show a significant influence on the PK parameters of imipenem. For pathogens with a MIC of 4 mg/L, the PTA target of 75% fT>MIC in patients with normal renal function was achieved when the imipenem was administered by a 4‐h infusion of 1 g q6h. Conclusion: The ECMO circuit had little effect on enhancing the PK changes of imipenem that had already occurred in these patients. A high dosage of imipenem may be required for achieving the PK/pharmacodynamic targets against less susceptible pathogens, however, the dosage regimens in patients with renal impairment may not need to be as high as those required in patients with normal renal function. ClinicalTrials.gov: NCT03858387.